Combination Therapy With Premixed & Basal Insulin Analogues in Asian Indians With Type 2 Diabetes - Srivastava, Brijendra Kumar (J Endocr Soc, 2021)
Many individuals with type 2 diabetes (T2DM) eventually need insulin for better glycaemic control. Different insulin regimens like basal, premixed, basal plus, split mixed and basal bolus are used in T2DM management. There is not much literature on a combination of premixed insulin in the morning along with basal insulin at night. Such a regimen is preferred by people with T2DM, who do not want to take an afternoon insulin dose due to inconvenience. To study the effect of a premixed insulin given in the morning and long acting basal insulin analogue given at night in T2DM subjects, we looked into this combination. We performed a retrospective study to look into the effects of premixed and basal insulin analogue combination in patients with T2DM (in addition to oral antidiabetic agents). From the diabetes electronic medical records of a tertiary care hospital for diabetes at Chennai in South India, 648 patients on premixed and basal insulin analogue combination, who came for a follow-up visit were included in the final analysis. Baseline characteristics included body weight, BMI, blood pressure, fasting lipid profile, fasting and post prandial plasma glucose and HbA1c were analysed at baseline, and a change in the parameters was studied at the first follow up visit between 5 to 7 months. Mean age of the study population was 60.7± 13.1 years with mean diabetes duration of 20.5 ± 8.0 years. Out of 648 patients included, three fifths were male. Statistically significant improvement was observed in body weight, BMI, HbA1c, systolic blood pressure, lipid profile, fasting blood sugars (P < 0.001) and post prandial blood sugars (P= 0.005) in comparison to baseline values. Significant reduction in HbA1c (1.7 %, p < 0.0001) was observed in those with in the highest tertile of HbA1c (11.3 ± 1.0 %) in comparison to the baseline values. At follow up, nearly a third of study subjects achieved a HbA1c target of < 8% (30.1 % vs 18.4 0%, p =0.0005) in comparison to the baseline values. 28.7 % patients on combination therapy achieved a fasting blood sugar value of < 130 mg/dl at follow up compared to 18.2 % patients at baseline (p <.0001). Similarly, 22 % of the patients on combination therapy also achieved post prandial blood sugars of <180 mg/dl at follow up, compared to 12.2 % (P<.0001) at baseline. This study shows that in T2DM subjects, a simple regimen of premixed and basal insulin analogue combination helps in improving the glycaemic control.